2006
DOI: 10.1071/wr05042
|View full text |Cite
|
Sign up to set email alerts
|

Indirect impacts of invasive cane toads (Bufo marinus) on nest predation in pig-nosed turtles (Carettochelys insculpta)

Abstract: The cane toad (Bufo marinus) was introduced into Australia in 1935. Because this toxic frog is novel to the Australian fauna, its introduction has impacted native fauna in a variety of ways. We anticipated a severe decline in the yellow-spotted monitor lizard (Varanus panoptes) associated with the arrival of cane toads along the Daly River, Northern Territory, and predicted a simultaneous impact on nest predation in the pig-nosed turtle (Carettochelys insculpta) because the lizard is the chief predator of C. i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(94 citation statements)
references
References 20 publications
3
91
0
Order By: Relevance
“…Direct population level impacts of cane toads have not been restricted to a single goanna species but a multitude of native predators in terrestrial and aquatic ecosystems including other monitor lizards, crocodiles, snakes and quolls (Shine 2010;. Doody et al (2006Doody et al ( , 2009Doody et al ( , 2013Doody et al ( , 2015 demonstrated that cane toad-induced decline of goannas can have cascading effects on species not predicted to be directly affected by cane toads such as small lizards, tree snakes, freshwater turtles and grain-eating birds in riparian systems in northern Australia. Cane toads have also been reported to have direct suppressive effects on their invertebrate prey, and to compete with nesting birds for burrows (Boland 2004;Greenlees et al 2007;.…”
Section: Discussionmentioning
confidence: 99%
“…Direct population level impacts of cane toads have not been restricted to a single goanna species but a multitude of native predators in terrestrial and aquatic ecosystems including other monitor lizards, crocodiles, snakes and quolls (Shine 2010;. Doody et al (2006Doody et al ( , 2009Doody et al ( , 2013Doody et al ( , 2015 demonstrated that cane toad-induced decline of goannas can have cascading effects on species not predicted to be directly affected by cane toads such as small lizards, tree snakes, freshwater turtles and grain-eating birds in riparian systems in northern Australia. Cane toads have also been reported to have direct suppressive effects on their invertebrate prey, and to compete with nesting birds for burrows (Boland 2004;Greenlees et al 2007;.…”
Section: Discussionmentioning
confidence: 99%
“…The arrival of toxic cane toads (Bufo marinus) in northern Australia precipitated a marked decline in V. panoptes, which in turn has seen the nest predation rate of pig nosed turtles (Carettochelys insculpta) decline from around 20 per cent to almost nothing [57]. Varanus panoptes has been suggested to have a similar impact on flatback (Natator depressus) and Olive Ridley (Lepidochelys olivacea) sea turtle populations owing to both their extensive use of turtle breeding habitat along the northern Australian coastline and the dominance of turtle eggs in their diet [58].…”
Section: Varanids and Prey Community Structurementioning
confidence: 99%
“…Nest predation by the yellow-spotted monitor lizard (Varanus panoptes) averaged nearly 20% during 1996-98 (11 to 25%) ). However, the arrival of invasive cane toads (Bufo marinus) in 2003 decimated populations of V. panoptes (Doody et al 2007), leading to no predation on Carettochelys nests in 2004 (Doody et al 2006). Daly River Carettochelys aggregate their nests, but probability of predation was not influenced by the number of nests on a beach (Doody et al 2003b).…”
Section: 6mentioning
confidence: 99%